Exercise for Depression: Cochrane systematic reviews are rigorous, but how subjective are the assessment of bias and the practice implications?. Issue 1 (April 2015) - Spedding, Simon
Abstract The Cochrane review Exercise for Depression and 12 previous systematic reviews support the view that exercise is as effective as conventional therapy for reducing symptoms of depression. However concerns remain about bias leading to downgrading of practice implications. The Cochrane 'Risk of Bias' tool is recognised as having poor reliability. So subjective judgements made about risk of bias and practice implications are discussed and compared with the response to doubtful blinding in antidepressant trials. Clinicians can explore the holistic management of depression including exercise based on the highest level of evidence.